Sustainable approach for enzyme augmentation in anaerobic membrane bioreactors - Loh, Carissa Mei Ling L. (2013)
Enhancing the hydrolysis of macromolecular extracellular polymeric substances and organic particulates with hydrolytic enzymes may potentially alleviate membrane fouling and solids accumulation in membrane bioreactors respectively. Prior studies investigating the effects of hydrolases on wastewater have been conducted, with positive results. As supplementing commercial enzymes may not be cost-feasible, in this study the recovery of hydrolases from wasted sludge was investigated.